Acute Partial Brown-Séquard Syndrome Secondary to Intraforaminal Disc Prolapse and Spinal Cord Infarction. (25th September 2019) - Astreinidis, Athanasios; Finitsis, Stephanos; Mavropoulou, Xanthippi; Psoma, Elisavet; Prassopoulos, Panagiotis
Abstract : We report the case of a 45-year-old female who presented with acute left abdominal pain and subsequently developed a left partial Brown-Séquard syndrome. Spinal fluid, inflammatory and prothrombotic tests were unremarkable. Magnetic resonance showed a left intraforaminal disc prolapse at the T9–T10 level and a hyperintense lesion on T2-weighted images in the left postero-lateral cord at the T8–T9 level with restricted diffusion on DWI imaging. A diagnosis of spinal cord infarction due to compromise of the left T8 thoracic radicular artery was made. The patient was managed conservatively and at the 3 months follow-up, she was ambulant and able to walk small distances without a walker.